Evaluation of the microbiome composition in particulate matter inside and outside of pig houses - Hong, Se-Woon; Park, Jinseon; Jeong, Hanna; Kim, Minseok (Journal of animal science and technology, 2021)
Particulate matter (PM) produced in pig houses may contain microbes which can spread by airborne transmission, and PM and microbes in PM adversely affect human and animal health. To investigate the microbiome in PM from pig houses, nine PM samples were collected in summer 2020 inside and outside of pig houses located in Jangseong-gun, Jeollanam-do Province, Korea, comprising three PM samples from within a nursery pig house (I-NPH), three samples from within a finishing pig house (I-FPH), and three samples from outside of the pig houses (O-PH). Microbiomes were analyzed using 16S rRNA gene amplicon sequencing. Firmicutes was the most dominant phylum and accounted for 64.8%-97.5% of total sequences in all the samples, followed by Proteobacteria (1.4%-21.8%) and Bacteroidetes (0.3%-13.7%). In total, 31 genera were represented by > 0.3% of all sequences, and only Lactobacillus, Turicibacter, and Aerococcus differed significantly among the three PM sample types. All three genera were more abundant in the I-FPH samples than in the O-PH samples. Alpha diversity indices did not differ significantly among the three PM types, and a principal coordinate analysis suggested that overall microbial communities were similar across PM types. The concentration of PM did not significantly differ among the three PM types, and no significant correlation of PM concentration with the abundance of any potential pathogen was observed. The present study demonstrates that microbial composition in PM inside and outside of pig houses is similar, indicating that most microbe-containing PM inside pig houses leaks to the outside from where it, along with microbe-containing PM on the outside, may re-enter the pig houses. Our results may provide useful insights regarding strategies to mitigate potential risk associated with pig farming PM and pathogens in PM.Particulate matter (PM) produced in pig houses may contain microbes which can spread by airborne transmission, and PM and microbes in PM adversely affect human and animal health. To investigate the microbiome in PM from pig houses, nine PM samples were collected in summer 2020 inside and outside of pig houses located in Jangseong-gun, Jeollanam-do Province, Korea, comprising three PM samples from within a nursery pig house (I-NPH), three samples from within a finishing pig house (I-FPH), and three samples from outside of the pig houses (O-PH). Microbiomes were analyzed using 16S rRNA gene amplicon sequencing. Firmicutes was the most dominant phylum and accounted for 64.8%-97.5% of total sequences in all the samples, followed by Proteobacteria (1.4%-21.8%) and Bacteroidetes (0.3%-13.7%). In total, 31 genera were represented by > 0.3% of all sequences, and only Lactobacillus, Turicibacter, and Aerococcus differed significantly among the three PM sample types. All three genera were more abundant in the I-FPH samples than in the O-PH samples. Alpha diversity indices did not differ significantly among the three PM types, and a principal coordinate analysis suggested that overall microbial communities were similar across PM types. The concentration of PM did not significantly differ among the three PM types, and no significant correlation of PM concentration with the abundance of any potential pathogen was observed. The present study demonstrates that microbial composition in PM inside and outside of pig houses is similar, indicating that most microbe-containing PM inside pig houses leaks to the outside from where it, along with microbe-containing PM on the outside, may re-enter the pig houses. Our results may provide useful insights regarding strategies to mitigate potential risk associated with pig farming PM and pathogens in PM.